Comparative effectiveness of umeclidinium/vilanterol versus inhaled corticosteroid/long-acting β2-agonist in patients with chronic obstructive pulmonary disease in a primary care setting in England - Czira, Alexandrosz; Requena, Gema; Banks, Victoria; Wood, Robert; Tritton, Theo; Castillo, Catherine M.; Yeap, Jie; Wild, Rosie; Compton, Chris; Rothnie, Kieran J.; Herth, Felix; Quint, Jennifer K.; et al. (The International journal of chronic obstructive pulmonary disease, 2023)
Comparing adherence to once-daily UMEC/VI, a long-acting muscarinic antagonist/long-acting β2-agonist and twice-daily inhaled corticosteroids in COPD